Corruption in Kyrgyzstan: The facts, causes and consequences - ÇOKGEZEN, MURAT (My University, 2004)
Despite the ongoing discussion on the merits of capitalism and market economy in the capitalist world, with the collapse of the Socialist regimes in Eastern Europe and the former Soviet Union, these newly, independent states decided to choose a new development model based on capitalism and market economy. When scholars realised differences in the economic performances among the former Socialist countries a decade after the transition process, the discussion on the relation between corruption and economic performance broadened. This paper aims to make a contribution on this discussion by evaluating the causes and consequences of corruption in one of the former Soviet republics, Kyrgyzstan. This paper is divided into five sections. Following this introduction the next section examines the causes and consequences of corruption based on previous studies in the field. Scholarly studies show that some common and country-specific factors promote corruption and, in turn, corruption weakens economic indicators. The third section, based on the World Bank corruption report, addresses the factors, arising from the reform movements in transition countries (TC) that have contributed to corruption, as well as the effects of corruption in TC. The fourth section studies the level, causes and consequences of corruption in Kyrgyzstan. All surveys, conducted by independent international organisations, showed that the level of corruption in Kyrgyzstan is very high. Accordingly, the study shows that all related economic indicators are negatively correlated with corruption level. This result shows that reducing corruption level will improve economic performance in Kyrgyzstan. An effective anti-corruption policy necessitates the determination of true causes that give way to corruption. Therefore, the causes of corruption in Kyrgyzstan are presented in this section as well. The final section provides conclusions. © 2004 Central Asian Survey.